2022
DOI: 10.4143/crt.2022.329
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local Treatment for Oligometastasis: A Comparability Based Meta-Analysis

Abstract: We intend to investigate the oncological efficacy and feasibility of local consolidative therapy (LCT) through a meta-analysis method. Materials and MethodsFour databases including Pubmed, Medline, Embase, and Cochrane library were searched.Target studies are controlled trials comparing outcomes of LCT versus a control group. Primary endpoints are overall survival (OS) and progression-free survival (PFS). ResultsA total of 54 studies involving 7,242 patients were included. Pooled analyses showed that the LCT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…These differences in inclusion criteria make it difficult to arrive at a strict definition of the oligometastatic state. In addition, a recent meta-analysis of both prospective RCTs and retrospective series by Rim et al [ 5 ], found that 48.1% of studies defined oligometastases as up to five lesions, 7.4% up to four lesions and 25.9% as up to 3 lesions. A recommendation from the European Society for Radiotherapy and Oncology (ESTRO) and the American Society for Radiation Oncology (ASTRO) asked participants if oligometastatic disease is defined by a maximum number of lesions and found that the consensus was that the ability to safely deliver curative radiation to metastasis determines the maximum number [ 6 ].…”
Section: Lesson #1: There May Never Be An Exact Cut-off For What Cons...mentioning
confidence: 99%
See 1 more Smart Citation
“…These differences in inclusion criteria make it difficult to arrive at a strict definition of the oligometastatic state. In addition, a recent meta-analysis of both prospective RCTs and retrospective series by Rim et al [ 5 ], found that 48.1% of studies defined oligometastases as up to five lesions, 7.4% up to four lesions and 25.9% as up to 3 lesions. A recommendation from the European Society for Radiotherapy and Oncology (ESTRO) and the American Society for Radiation Oncology (ASTRO) asked participants if oligometastatic disease is defined by a maximum number of lesions and found that the consensus was that the ability to safely deliver curative radiation to metastasis determines the maximum number [ 6 ].…”
Section: Lesson #1: There May Never Be An Exact Cut-off For What Cons...mentioning
confidence: 99%
“…Of the eight positive trials listed, five used SABR only [ 3 , 4 , 12 , 13 , 16 ], one used RFA [ 7 ], and two allowed radiation and/or surgery but approximately 75% of those patients received radiation [ 2 , 11 ]. A meta-analysis of 54 prospective and retrospective studies also found that 77.8% used radiation, 46.3% used surgery and 18.5% used RFA as the modality of choice for local consolidative therapy in oligometastases [ 5 ].…”
Section: Lesson #3: In Choosing a Treatment Modality The Evidence Bes...mentioning
confidence: 99%
“…However, there are still no clinically biomarkers or other techniques to identify oligometastasis that can distinguish the real oligometastatic state from a rapidly of oligometastatic NSCLC and elucidating its potential difference from the polymetastasis will enable a more thorough selection of patients with a low metastatic burden in whom local radical treatment integrated into multimodality regime can be applied to all metastatic sites. Systemic therapies, including targeted therapies and immunotherapy, combined with local treatments such as surgery, stereotactic ablative radiotherapy or thermal ablation can indeed obtain a long-term survival with promising progression-free survival (PFS) or overall survival (OS) [6][7][8][9] in oligometastatic NSCLC. Previous researches on actionable genomic alterations for targeted therapies and predictive biomarkers of immunotherapy mainly focused on populations of conventional NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…
The first use the term "oligometastasis' in the literature was done by Hellman and Weichselbaum, who also built its concept as "the status between localized and widely metastatic" [1]. Though not all previous trials that evaluated the role of local aggressive treatment (LAT) in oligometastatic settings were affirmative, it cannot be denied that LAT has a strong tendency of improving clinical outcomes, which was elucidated through the effort of Oligometastasis Working Group of Korea Cancer Association [2]. As the meaning of the prefix "oligo-", with Latin origin, contains "few, small, or little" in number, the definition of oligometastasis has mostly been based on the metastatic lesion number, and most clinical trials, in fact, have adopted the number-based definition.
…”
mentioning
confidence: 99%